Integration of Building Information Modeling and Geographic Information Systems for Efficient Airport Construction Management - Alessandro Di Graziano; Eliana Ragusa; Giancarlo Guarrera (Future Transportation, 2025)
This study analyzes the use of new technologies, such as building information modeling (BIM), to simplify process management in the Architecture, Engineering, and Construction sector. By providing dynamic, realistic system models, BIM enables innovative collaboration within a common data environment. In that context, this study focuses on the operational management of construction sites. Recognizing the limitations of BIM for spatial analyses, this research integrates geographic information systems (GIS) through a three-phase methodology: (a) development of BIM models; (b) definition of geographic information within the GIS; (c) BIM-GIS integration. To demonstrate the effectiveness of the methodology, the research applies it to a case study on managing an airport construction site, focusing on obstacles and hazards for air navigation. However, the methodology identified in this study is generalizable and could be adapted for other applications with proper calibration of the required information parameters. The application highlights the potential of integrating GIS and BIM systems, particularly for safety and operational management. However, inherent structural differences between the two systems often require model simplifications, especially in complex projects. The study also reveals that GIS-BIM interoperability is not always seamless, emphasizing the need for further research to enhance integration processes and improve system compatibility in future applications.